Eruptive timing and 200 year episodicity at 92°W on the hot spot‐influenced Galapagos Spreading Center derived from geomagnetic paleointensity - Julie A. Bowles; Alice Colman; J. Timothy McClinton; John M. Sinton; Scott M. White; Kenna H. Rubin (Geochemistry, Geophysics, Geosystems, 2014)
Abstract Eruptive timing in mid‐ocean ridge systems is relatively poorly constrained, despite being an important variable in our understanding of many mid‐ocean ridge processes, including volcanic construction; magma recharge, flux, and storage; and the stability of hydrothermal systems and biological communities. Only a handful of absolute eruption chronologies exist, yet they are essential in understanding how eruptive timing varies with important controlling variables. To construct an eruptive history at one location on the Galapagos Spreading Center, we present age determinations derived from geomagnetic paleointensity. To aid interpretation of the paleointensity data, we also present results from on‐bottom magnetic anomaly measurements and forward modeling of topographic‐induced magnetic anomalies. Anomalies may lead to a 1–2 µT bias in flow‐mean paleointensities, which does not significantly affect the overall interpretation. Paleointensity results for the three youngest sampled units are indistinguishable, consistent with the flows being emplaced in relatively rapid succession. Comparisons with models of geomagnetic field behavior suggest these flows were erupted sometime in the past 100–200 years. The fourth sampled unit has a significantly higher paleointensity, consistent with an age of roughly 400 years. The possible bias in paleointensity data allows for ages as young as ∼50 years for the youngest three flows and 200–400 years for the oldest flow. This age distribution demonstrates an episodicity in the emplacement of the largest flows at this location, with a 200–300 year period of relative quiescence between emplacement of the oldest unit and the three youngest units.